Pengaruh FOMO dan Boredom Proneness terhadap Perilaku Phubbing pada Gen Z Pengguna Social Media di Karawang - Nababan, Giovani Effenbert; Riza, Wina Lova; Aisha, Dinda (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
In Indonesia, there is a term "generation bowing". It is focused on individuals who will generally focus more attention on smartphones with their head down gesture, which is then manifested through a way of behavior known as phubbing. The purpose of this study is to determine how FOMO and boredom proneness affect phubbing behavior in Gen Z social media users in Karawang. This study used a quantitative method with a sample of 208 participants consisting of 64 men and 144 women born between 1995 and 2010. Data analysis using multiple linear regression tests using the SPSS version 25.0 for windows program. The scales used in the results of this study are the fear of missing out scale (FOMOS), a short boredom proneness scale (SBPS), and generic phubbing scale (GPS). According to the results of the T and F tests, with a significance of 0.000 <0.05, it shows that there is an influence of FOMO and boredom proneness on phubbing behavior by 43.2%.